Small Scale, High Precision: Robotic Surgery in Neonatal and Pediatric Patients-A Narrative Review - Emil Radu Iacob; Roxana Iacob; Laura Andreea Ghenciu; Tudor-Alexandru Popoiu; Emil Robert Stoicescu; Calin Marius Popoiu (MDPI AG, 2024)
This narrative review explores the evolution and implications of robotic-assisted surgery in pediatric and neonatal cases, focusing on its advantages, drawbacks, and the specific diseases amenable to this innovative technology. Following PRISMA guidelines, 56 relevant articles from the past five years were selected, emphasizing advancements in precision, reduced trauma, and expedited recovery times for pediatric patients. Despite challenges like cost and training, ongoing research shapes pediatric robotic-assisted surgery, promising improved outcomes. The technology's benefits include enhanced precision, minimized scarring, and faster recovery, addressing the challenges in delicate pediatric procedures. Challenges encompass cost, training, and instrument design, but ongoing refinements aim to overcome these. This review underscores psychological and musculoskeletal considerations for patients and surgeons. While acknowledging limitations and preferred pathologies, this review outlines the transformative potential of robotic-assisted surgery in reshaping pediatric surgical care. This comprehensive assessment concludes that, despite challenges, ongoing advancements promise a future of enhanced precision and tailored care in pediatric surgery.